Comparative Study between Operative versus Non-operative Treatment for Base of Fifth Metatarsal Fractures in Young Adults - KC, K. M.; Marahatta, S. B.; Niroula, A.; KC, A.; Pangeni, R. B. (Kathmandu University Medical Journal, 2021)
Background The treatment of displaced base of fifth metatarsal fracture remains controversial regarding the conservative and operative treatment. Objective To investigate the therapeutic effect of operative and non-operative treatment for base of fifth metatarsal fractures. Method This was retrospective comparative study performed in Civil Service Hospital, Kathmandu, Nepal from December 2014 to November 2019. Patients were randomly divided into two groups by computer generated technique. Group1 included 17 patients who underwent open reduction and internal fixation using tension band wiring, whereas group 2 included 17 patients who underwent non-operative treatment with boot cast. Result The AOFAS and VAS-FA scores at 3 months in operative and non-operative groups were 89.34±2.14 versus 86.94±2.22 (p < 0.05) and 5.58±0.87 versus 3.58±0.93 (p < 0.05). Similarly, AOFAS and VAS-FA at 12 months after treatment were 90.94±2.43 versus 90.17±1.55 (p > 0.05) and 0.64±0.280.94±0.39 (p > 0.05) in operative and non-operative groups respectively. The average time to bear full weight and return to work were 6.82±1.13 versus 7.08±1.24 weeks (p > 0.05) and 8.76±1.20 versus 10.35±1.41 weeks ( p < 0.05) respectively. The mean of VAS score at 3months of treatment is 5.58±0.87 for non-operative group and 3.58±0.93 for operative group (p <0.05). Conclusion Operative intervention has been preferred over the non-operative treatment in young adults or athletes with more than 3 mm displaced fifth metatarsal base fracture to achieve anatomical reduction of fracture, hasten the recovery and rehabilitation and to decrease the complications associated with non-operative treatment.